2016
DOI: 10.1007/s10708-016-9703-5
|View full text |Cite
|
Sign up to set email alerts
|

Orientation information in wayfinding instructions: evidences from human verbal and visual instructions

Abstract: Although the importance of landmarks for human navigation and for orientation is well accepted, most of today's navigation systems hardly incorporate any landmark information or information supporting orientation. Different from previous research that only addressed turn-by-turn instructions in verbal forms and landmarks at decision points, the present study provides empirical evidence that human-generated wayfinding instructions are not solely turn-by-turn but the majority of instructions provide orientation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…It was shown that people include landmarks in route instructions, both at decision points and along the route [18][19][20][21][22]. Moreover, it was shown that besides local landmarks, global landmarks, i.e., off-route landmarks with sufficiently large reference region, are important features in human wayfinding instructions [23][24][25][26]. In contrast to contemporary turn-by-turn-based wayfinding support systems, human wayfinding instructions contain a significant amount of orientation information that support the acquisition of configurational knowledge [23].…”
Section: Landmarks and Orientation Information In Wayfinding Instructmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that people include landmarks in route instructions, both at decision points and along the route [18][19][20][21][22]. Moreover, it was shown that besides local landmarks, global landmarks, i.e., off-route landmarks with sufficiently large reference region, are important features in human wayfinding instructions [23][24][25][26]. In contrast to contemporary turn-by-turn-based wayfinding support systems, human wayfinding instructions contain a significant amount of orientation information that support the acquisition of configurational knowledge [23].…”
Section: Landmarks and Orientation Information In Wayfinding Instructmentioning
confidence: 99%
“…Moreover, it was shown that besides local landmarks, global landmarks, i.e., off-route landmarks with sufficiently large reference region, are important features in human wayfinding instructions [23][24][25][26]. In contrast to contemporary turn-by-turn-based wayfinding support systems, human wayfinding instructions contain a significant amount of orientation information that support the acquisition of configurational knowledge [23]. Orientation information is considered to be any information, including local and global landmarks, that supports people to derive their position in space and orient themselves regarding known environmental information [27].…”
Section: Landmarks and Orientation Information In Wayfinding Instructmentioning
confidence: 99%
“…These services not only offer maps for free [8,9], they also provide route planning functions [10,11]. Additionally, landmarks, salient objects in the environment [12][13][14], are represented in these maps as pictograms. Landmark representations not only support the formation of a cognitive map, they also facilitate orientation, as users can match them to surrounding landmarks in the environment and thereby triangulate their current positions [12,13,15].…”
Section: Introductionmentioning
confidence: 99%
“…Structural salience on the other hand represents the degree of visual attention allocated towards an object based on its relative position to a specified route [16,28]. In navigation tasks, four types of route elements relevant for wayfinding instructions and route knowledge [13,29,30] can be distinguished (see Fig 1). Decision points are positions where at least two road branches exist (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, along the route at decision points, it would be helpful to distinguish different geometries of landmarks-point-like, linear, etc. The size and shape of the landmark bear useful information for wayfinding instructions [50]. Additionally, adjustments could be done to match a local culture, urban density, and scale.…”
Section: Discussion and Future Workmentioning
confidence: 99%